Effect of Mouriri pusa tannins and flavonoids on prevention and treatment against experimental gastric ulcer - Vasconcelos, P. C. P.; Andreo, M. A. [UNESP]; Vilegas, Wagner [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Pellizzon, C. H. [UNESP] (Elsevier B.V., 2010)
Aim of the study: Mouriri pusa, popularly known as manapuca or jaboticaba do mato, is a plant from Brazilian cerrado that has been found to be commonly used in the treatment of gastrointestinal disturbs in its native region. The present work was carried out to investigate the effect of tannins (TF) and flavonoids (FF) fractions from Mouriri pusa leaves methanolic extract on the prevention and cicatrisation process of gastric ulcers, and also evaluate possible toxic effects.Materials and methods: The following protocols were taken in rats: acute assay, in which ulcers were induced by oral ethanol after pre-treatment with the fractions; and 14 days treatment assay, in which ulcers were treated for 14 days after induction by local injection of acetic acid.Results: In the acute model, treatment with either, TF (25 mg/kg) or FF (50 mg/kg), was able to reduce lesion area, showing gastroprotective effect. In addition, FF proved itself anti-inflammatory by reducing COX-2 levels. In acetic acid model, both fractions exhibited larger ulcers' regenerative mucosa, indicating cicatrisation enhancement. FF group also showed augmented cell proliferation, anti-inflammatory action and enhanced angiogenesis as well as increased mucus secretion. Moreover, concerning the toxicity parameters analyzed, no alteration in the fractions groups was observed.Conclusions: Tannins and flavonoids from Mouriri pusa provide beneficial effects against gastric ulcers with relative safety. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Tannins; Flavonoids; Melastomataceae; Gastric ulcer; Mouriri pusa